Host Plants and Climate Structure Habitat Associations of the Western Monarch Butterfly - Dilts, Thomas E.; Steele, Madeline O.; Engler, Joseph D.; Pelton, Emma M.; Jepsen, Sarina J.; McKnight, Stephanie J.; Taylor, Ashley R.; Fallon, Candace E.; Black, Scott H.; Cruz, Elizabeth E.; Craver, Daniel R.; Forister, Matthew L. (Frontiers in Ecology and Evolution, 2019)
The monarch butterfly is one of the most easily recognized and frequently studied insects in the world, and has recently come into the spotlight of public attention and conservation concern because of declining numbers of individuals associated with both the eastern and western migrations. Historically, the larger eastern migration has received the most scientific attention, but this has been changing in recent years, and here we report the largest-ever attempt to map and characterize non-overwintering habitat for the western monarch butterfly. Across the environmentally and topographically-complex western landscape, we include 8,427 observations of adults and juvenile monarchs as well as 20,696 records from thirteen milkweed host plant species. We find high heterogeneity of suitable habitat across the geographic range, with extensive concentrations in the California floristic province in particular. We also find habitat suitability for the butterfly to be structured primarily by host plant habitat associations, which are in turn structured by a diverse suite of climatic variables. These results add to our knowledge of range and occupancy determinants for migratory species and provide a tool that can be used by conservation biologists and researchers interested in interactions among climate, hosts and host-specific animals, and by managers for prioritizing future conservation actions at regional to watershed scales.